Biosynthetic engineering of nonribosomal peptide synthetases‡. (28th July 2016) - Kries, Hajo
Abstract : From the evolutionary melting pot of natural product synthetase genes, microorganisms elicit antibiotics, communication tools, and iron scavengers. Chemical biologists manipulate these genes to recreate similarly diverse and potent biological activities not on evolutionary time scales but within months. Enzyme engineering has progressed considerably in recent years and offers new screening, modelling, and design tools for natural product designers. Here, recent advances in enzyme engineering and their application to nonribosomal peptide synthetases are reviewed. Among the nonribosomal peptides that have been subjected to biosynthetic engineering are the antibiotics daptomycin, calcium‐dependent antibiotic, and gramicidin S. With these peptides, incorporation of unnatural building blocks and modulation of bioactivities via various structural modifications have been successfully demonstrated. Natural product engineering on the biosynthetic level is not a reliable method yet. However, progress in the understanding and manipulation of biosynthetic pathways may enable the routine production of optimized peptide drugs in the near future. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Driven by rapid progress in enzyme engineering and design technologies, new tools are being explored for the redesign of nonribosomal peptide synthetases. Recent examples for successful nonribosomal peptide synthetase redesign by domain swapping, directed evolution and active site mutagenesis are highlighted in this review. Tailoring of peptide natural products is a promising approach in the fight against antibiotic resistance.